If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + 14 = 2x + 14 Reorder the terms: 14 + 3z = 2x + 14 Reorder the terms: 14 + 3z = 14 + 2x Add '-14' to each side of the equation. 14 + -14 + 3z = 14 + -14 + 2x Combine like terms: 14 + -14 = 0 0 + 3z = 14 + -14 + 2x 3z = 14 + -14 + 2x Combine like terms: 14 + -14 = 0 3z = 0 + 2x 3z = 2x Solving 3z = 2x Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Divide each side by '3'. z = 0.6666666667x Simplifying z = 0.6666666667x
| .25r+9=10-.75r | | -7x+35=7x-35 | | 0.12x=0.6 | | 225=10(x-65)+75 | | 0.7h=-0.112 | | 5x-7=2x+33 | | f(-3)=x^2+3 | | 2x-5y=-23 | | 1600x=950x+211,250 | | 5x-17=180 | | 1600x=950+211,250 | | -12f=-180 | | 7x-(12)=3x | | -13a=52 | | 3x=7x-(12) | | z-8z=9z-1-z | | 0=x^4+16x^2-36 | | 9b-10=(-b)-18 | | -10x+14-3x=-12 | | 60t=45(t+1) | | 8f+11=-7f-(19) | | 2y^2+2y-24=0 | | -(6x-12)= | | -9=3x-17 | | x^6+x= | | 5z-(43)=2z+80 | | 21x^2-18x-20=0 | | -4x+5y=-35 | | 16x+8=24 | | 10x-3=2x+21 | | 2Logx=2 | | 13q-(48)=-3q |